The infinite desire for growth - Cohen, Daniel 1953- (Highbridge Audio, 2019)
The Infinite Desire for Growth spotlights the obsession with wanting more, and the global tensions that have arisen as a result. Amid finite resources, increasing populations, environmental degradation, and political unrest, the quest for new social and individual goals has never been so critical. Leading economist Daniel Cohen provides a whirlwind tour of the history of economic growth, from the early days of civilization to modern times, underscoring what is so unsettling today. The new digital economy is establishing a "zero-cost" production model, inexpensive software is taking over basic tasks, and years of exploiting the natural world have begun to backfire with deadly consequences. Working hard no longer guarantees social inclusion or income. Drawing on economics, anthropology, and psychology, and thinkers ranging from Rousseau to Keynes and Easterlin, Cohen examines how a future less dependent on material gain might be considered and, how, in a culture of competition, individual desires might be better attuned to the greater needs of society. At a time when wanting what we haven't got has become an obsession, The Infinite Desire for Growth explores the ways we might reinvent, for the twenty-first century, the old ideal of social progress